ANALISIS PENGEMBANGAN ELECTRONIC GOVERNMENT DI KOTA TEGAL - Thalita rifda Khaerani; Melsy Vanesa Sarai (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
The application of e-government to an area referred to Legislation No. 32 in 2004 the legitimacy of territory administration. Hence, the construction of a government that is supposed to have transparent joint controls in order for a government to be built to run with public interests. In this case the e-government would appear to be an alternative to doing well, especially in the service sector. Therefore e-government development efforts in the City of Tegal are required in support of smart city in the City of Tegal. The study aims to analyze development based on three successful e-government elements in the city's tegal government as well as factors that determine e-government readiness levels in the city's tegal. The kind of research is qualitative desktop research with information-selection techniques, data collection techniques of observation, in-depth interviews, documentation and library studies and data analysis techniques of data reduction, presentation of data and drawing conclusions. Studies obtained that in the application of the e-government in terms of the quality of human resources are adequate, and then the administration is well executed. But in the process there is still a shortage which makes the implementation less maximum. Which is in a regulatory way, infrastructure, nor the lack of human resource.